Current approach for the prosthesis patient mismatch - Asuman Biçer Yeşilay; Zekeriya Kaya; Recep Demirbağ (KARE Publishing, 2013)
All prosthetic valves are at least mildly stenotic and have relatively high transvalvular pressure gradients that can be observed despite normal prosthesis function. Such gradients may be due to a mismatch between prosthesis effective orifice area (EOA) and patient's body size. Valve prosthesispatient mismatch (VP-PM) may occur due to mismatches of both parameters, the expected hemodynamic performance of the prosthesis and the cardiac output requirements of the patient, which are largely related to the body size at rest. In other words, a prosthesis may be adequate for patients with a small body surface area (BSA) but might become obstructive for patients with a large BSA. The only parameter that has proven to be consistently and realistically useful to predict and describe VP-PM is the effective orifice area index (EOAI). The projected EOAI was identified as the best parameter to predict the VP-PM occurrence after surgery. VP-PM has been known to be independently and significantly associated with clinical outcomes. Severe VP-PM has a significant impact on early and late mortality, whereas moderate VP-PM may have a significant effect on mortality only in vulnerable subsets of patients, and particularly in those with depressed LV systolic function. The surgeon's anticipation of VP-PM prior to surgery, and successfully implented preventive strategies can reduce the incidence of VP-PM. Preventive strategies to avoid VPPM should be individualized according to the anticipated severity of VP-PM and of the patient's baseline risk profile.